Analisis Wacana Penerjemahan Iklan Nike - Ariestya, Siti Alfa (Kementerian Sekretariat Negara Republik Indonesia, 2018)
The Nike advertisement is famous for its simple yet meaningful logo and slogan, Just Do It. The use of simple words makes the Nike advertisement easy to remember. This study aims to describe the discourse analysis on the Nike advertisement translation, and utilizes data from digital media or the internet. This study is a descriptive qualitative one that uses the Agih method, which is a method where the instrument is its own language, namely the written discouse. The results of the study show that the Nike advertisement uses brief words, which makes the products stand out, and applies superlative and comparative words to get distinctive effects. Key words: advertisement, Nike, discourse, agih method